Towards Industry Improvement in Manufacturing with DMAIC - Acosta Vargas, Patricia (2020)
Today, the accelerated development of industry 4.0 and the immer- sion of technologies with the DMAIC methodology, Lean Manufacturing allows higher productivity and continuous improvement of industrial processes. There are countless manufacturing companies, of which very few have invested in tech- nology and methodologies, so they have not been able to prepare themselves to advance at the same pace as the industrial revolution. This research proposes to include improvements in the manufacture of furniture by applying software tools and methodologies such as DMAIC, which consists of combining the application of some tools such as Lean, visual management, and standardized work. As a case study, we applied to the manufacture of furniture; the results indicated that by applying DMAIC and simulation tools, a signiﬁcant increase in production was achieved, with a decrease in delivery time, in addition to the optimization and reduction of waste. This research can serve as a reference for future studies related to manufacturing processes when applying DMAIC, Lean Manufacturing, and simulation software.